2021 International Symposium on Wearable Computers 2021
DOI: 10.1145/3460421.3478821
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Freezing of Gait with Earables Trained from VR Motion Capture Data

Abstract: Freezing of Gait (FoG) is a common disabling motor symptom in Parkinson's Disease (PD). Auditory cueing provided when FoG is detected can help mitigate the condition, for which earables are potentially well suited as they are capable of motion sensing and audio feedback. However, there are no studies so far on FoG detection at the ear. Immersive Virtual Reality (VR) combined with video-based full-body motion capture has been increasingly used to run FoG studies in the medical community. While there are motion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…In several studies, it has been shown that VR systems are often composed of physiological and motion acquisition sensors. These technologies can be extended to detection and intervention on FoG episodes 89 . In 2021, Chen et al 90 studied the effects of a week training with VR device.…”
Section: Virtual Reality Devicesmentioning
confidence: 99%
“…In several studies, it has been shown that VR systems are often composed of physiological and motion acquisition sensors. These technologies can be extended to detection and intervention on FoG episodes 89 . In 2021, Chen et al 90 studied the effects of a week training with VR device.…”
Section: Virtual Reality Devicesmentioning
confidence: 99%